The struggles of breastfeeding mothers of preterm infants: a qualitative study - Ling Chen; Yanyan Shang; Xuqi Tian; Yingjuan Huang; Yu Sun; Chunhua Fu; Jinbing Bai; Yanqun Liu (BMC Pregnancy and Childbirth)
Abstract Background Breast milk, with its rich bioactive components and numerous maternal and infant health benefits, is globally recommended as the ideal food for babies, especially premature infants. With the elevated incidence of premature births, suboptimal breastfeeding rates are detrimental, especially considering numerous efforts to promote breastfeeding. The reasons for breastfeeding cessation remain unclear. This study utilizes the social-ecological system theory to explore reasons for the cessation of breastfeeding among mothers of premature infants in China. Methods An interpretive phenomenological research design was implemented in Wuhan. Through purposive sampling, 14 mothers of premature infants who had discontinued breastfeeding were recruited in Wuhan, China. Semi-structured interviews were conducted to collect data guided by an interview outline developed by the theoretical framework. Content analysis was applied to analyze the interview data. Results The overarching theme of this study was: “On the journey of breastfeeding, who will hold up the sky for me?” This theme encapsulated the multifaceted challenges faced by mothers before discontinuing breastfeeding and their urgent need for comprehensive support. For these mothers, breastfeeding represented not only a physiological challenge but also a significant psychological and emotional burden. The analysis identified three primary categories: Microsystems—the challenges of breastfeeding and adaptation barriers; Mesosystems—dysfunctional support systems within families and hospitals; and Macrosystems—insufficient social support systems. Conclusions Mothers of premature infants experienced weakened breastfeeding support systems, highlighting the need for (1) Enhancing psychological support and targeted breastfeeding guidance for mothers of preterm infants; (2) Establishing an evidence-based, coordinated support system that integrates hospital and family networks; (3) Strengthening monitoring and enforcement mechanisms for birth policies, enhancing breastfeeding facilities in public spaces, and improving the capacity for breastfeeding education and promotion within communities.